Human Blood CXCR5(+)Foxp3(+) T cells Are Indicators of Ongoing Humoral Activity Not Fully Licensed With Suppressive Function - Fonseca, Valter R (Sci Immunol, 2017)
Germinal center (GC) responses are controlled by T follicular helper (Tfh) and T follicular regulatory (Tfr) cells and are crucial for the generation of high affinity antibodies. Although the biology of human circulating and tissue Tfh cells has been established, the relationship between blood and tissue Tfr cells, defined as CXCR5(+)Foxp3(+) T cells, remains elusive. Here, we found that blood Tfr cells are increased in Sjögren syndrome, especially in patients with high autoantibody titres, as well as in healthy subjects upon influenza vaccination. While, blood Tfr cells correlated with humoral responses they lack full B-cell suppressive capacity, despite being able to suppress T-cell proliferation. Blood Tfr cells have a naïve-like phenotype, although they are absent from human thymus or cord blood. Here, we found these cells were generated in peripheral lymphoid tissues prior to T-B interaction, as they are maintained in B-cell deficient patients. Therefore, blood CXCR5(+)Foxp3(+) T cells in human pathology indicate ongoing humoral activity, but are not competent Tfr cells.